Analisis Pengaruh Struktur Kepemilikan Institusional, Keputusan Pendanaan, Keputusan Investasi Dan Kebijakan Deviden Terhadap Nilai Perusahaan (Studi Empiris Pada Perusahaan Manufaktur di Bursa Efek Indonesia) - Rachmasari, Annisa; Kaluge, David (JAE (JURNAL AKUNTANSI DAN EKONOMI), 2019)
This study aims to obtain empirical evidence about the structure of institutional ownership of funding decisions, investment decisions, dividend policies that have a positive effect on firm value. Dependent variable Corporate value is calculated using Tobin’s Q, the independent variable uses the institutional ownership structure, DER, investment decision, DPR. Population is a manufacturing company listed on the Indonesia Stock Exchange in 2017. Sampling used a purposive sampling method and obtained as many as 41 companies. This study used Wald's multiple linear regression method and moderate regression analysis. The results of the study indicate that the structure of institutional ownership, funding decisions, investment decisions, and dividend policies have a positive effect on firm value. Keywords: institutional ownership, funding decisions, investment decisions, dividend policy, company value